2014
DOI: 10.1007/s10637-014-0083-8
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of the gamma secretase inhibitor RO4929097 in patients with previously treated metastatic pancreatic adenocarcinoma

Abstract: Purpose The notch pathway is overexpressed in pancreatic adenocarcinoma. RO4929097, an oral inhibitor of the γ-secretase enzyme has been safely given as a single agent in patients with advanced solid tumors. We aimed to evaluate the efficacy of RO4929097 in patients with pancreatic adenocarcinoma (PDA). Methods A two-stage, single-arm Phase II trial was conducted in patients with previously treated metastatic PDA. RO4929097 was administered at a dose of 20 mg daily on days 1-3, 8-10 and 15-17 of 21-day cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 19 publications
(20 reference statements)
1
56
0
Order By: Relevance
“…GSI with drugs including RO4929097, a small and potent inhibitor of γ‐secretase, lead to the blockade of Notch signaling in tumor cells, and the significant antitumor effects of GSIs have been verified in preclinical studies . Nevertheless, in a current phase II study performed in patients with pancreatic adenocarcinoma, colorectal cancer and EOC, RO4929097 showed minimal clinical activity and the median progression‐free survival time was not superior relative to historical treatment data . Based on our data, we propose two reasons that may partly explain the underwhelming clinical response to RO4929097, and we suggest strategies to improve the objective responses to this GSI.…”
Section: Discussionmentioning
confidence: 65%
“…GSI with drugs including RO4929097, a small and potent inhibitor of γ‐secretase, lead to the blockade of Notch signaling in tumor cells, and the significant antitumor effects of GSIs have been verified in preclinical studies . Nevertheless, in a current phase II study performed in patients with pancreatic adenocarcinoma, colorectal cancer and EOC, RO4929097 showed minimal clinical activity and the median progression‐free survival time was not superior relative to historical treatment data . Based on our data, we propose two reasons that may partly explain the underwhelming clinical response to RO4929097, and we suggest strategies to improve the objective responses to this GSI.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, γ-secretase inhibitors are in clinical trials for other human cancers [49,50]. Likewise, Wnt signaling inhibitors may also be considered for treatment of HBV-associated HCCs [51].…”
Section: Discussionmentioning
confidence: 99%
“…29 GSIs possess potent antitumour activity to inhibit cell growth and induce cell apoptosis in many human cancers, such as breast cancer, hepatoma, myeloma, and pancreatic cancer, and some of them have already been tested in clinical trials. 30,31,32,33,34 Thus, to investigate the effect of Notch-1 inhibition on DTX-resistant LAD, we introduced a widely used GSI DAPT. Our data revealed that inhibition of Notch-1 by DAPT sensitizes resistant LAD cells to DTX treatment in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%